Delayed loss of control of plasma lipopolysaccharide levels after therapy interruption in chronically HIV-1-infected patients. - Papasavvas, Emmanouil; Pistilli, Maxwell; Reynolds, Griffin; Bucki, Robert; Azzoni, Livio; Chehimi, Jihed; Janmey, Paul A; DiNubile, Mark J; Ondercin, Joe; Kostman, Jay R; Mounzer, Karam C; Montaner, Luis J (AIDS (London, England), 2009)
Increased circulating levels of lipopolysaccharide (LPS) have been demonstrated in HIV-1-infected progressors. We investigated the effect of antiretroviral therapy (ART) interruptions on plasma LPS levels.
Keywords: Adolescent; Adult; Anti-HIV Agents; Antigens, CD14; CD4 Lymphocyte Count; Drug Administration Schedule; Endotoxins; HIV Infections; HIV-1; Humans; Lipopolysaccharides; Lymphocyte Activation; T-Lymphocyte Subsets; Viral Load; Viremia; Virus Replication; Young Adult